Estudo e desenvolvimento de um conversor formador de rede multiterminal - Renata Cristina da Silva (2020)
Distributed generators are connected to the distribution system and supply power to the loads connected to it and the main grid in case of surplus power. Therefore, microgrids were conceived, which have GD, loads, and energy storage and operates connected the grid and in island mode. When a microgrid is connected to the main grid, it is said to operate in grid-connected mode and if the microgrid operates without any connection to the main grid, it is classified as islanded operation. For islanded operation, it is necessary to have a grid-forming converter to establish the voltage and frequency at the point of common coupling (PCC), which in case of grid-connected mode was done by the main grid. The purpose of this work is the study, development, and construction of a low voltage grid-forming converter to be used in a microgrid and that has 5.1kW of rated power. DC/DC converters connected to the grid-forming converter are used to manage the active power transfer from the photovoltaic array (PV) and energy storage system made of batteries. The system is designed to work in grid-connected mode supplying power to the microgrid or charging the batteries and in islanded mode performing the function of grid-forming, that is, establishing the voltage and frequency at the PCC. For the converter, current and voltage control loops are implemented for the control of the active and reactive power injected to the grid in grid-connected mode and control of the voltage's amplitude and the frequency at the PCC in islanded mode. The PV and batteries produce the active power necessary to supply the load in islanded mode. Additionally, for this working mode DC bus signaling (DBS) is implemented where DC/DC converters change their operation mode accordingly to the voltage level at the DC bus. This work presents the elements of the converter and its mathematical modeling and the design of the control strategy used. Analysis of the project is carried out by simulation and practical implementation of the system, where the performance in the various operating modes is examined. Processing and control algorithms are implemented in FPGA, model sbRIO9606, from National Instruments and controlled by supervisory designed with LabVIEW.